Digitalizing MSMEs: A Modern Financial Strategy To Improve The Quality of Decision-Making - Tio Arriela Doloksaribu; Dwi Ekasari Harmadji; Fitrotin Azizah (PT Keberlanjutan Strategis Indonesia, 2026)
The economic transformation in the heritage area of ​​Malang City has driven the growth of MSME cafes, but entrepreneurs still face complex accounting and cash flow management challenges. This study aims to analyze the influence of mental budgeting and financial literacy on the quality of business decision-making, and to examine the role of accounting digitalization as a moderating variable. Using a quantitative explanatory approach based on the Resource-Based View (RBV) framework, the study population was MSME cafe owners in the heritage area of ​​Malang City. The number of 120 sample was determined through purposive sampling with the criteria of entrepreneurs who have adopted a digital recording system for at least one year. The results of hypothesis testing indicate that mental budgeting and financial literacy have a positive and significant effect on the quality of decision-making, with financial literacy as the strongest predictor. Furthermore, accounting digitalization is proven to significantly play a role as a moderating variable that strengthens the relationship between the two independent variables on the quality of business decisions. These findings confirm that individual cognitive abilities, supported by technology-based dynamic capabilities, can transform subjective financial information into data-driven strategic decisions. Theoretically, this research extends the behavioral accounting and RBV literature to the creative sector. Practically, this research has implications for MSME owners in integrating digital record-keeping and serves as a reference point for the Malang City Government in formulating more inclusive and effective digital financial training policies.